THE IMPACT OF PERCEIVED RISK, PERCEIVED BENEFIT, AND TRUST ON CUSTOMER INTENTION TO USE TOKOPEDIA APPS - Hesti Candra Sari (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2022)
This study aims to analyze the influence of perceived benefit and perceived risk on trust and intention to use Tokopedia, as a biggest marketplace in Indonesia. This study using descriptive quantitative method to analyze 150 responden with Partial Least Square. The results of the study indicate a positive correlation between the perceived benefit and trust of Tokopedia users, which leads to an increase in the intention to use the application. Additionally, the results of the study demonstrate a negative correlation between perceived risk and trust in the Tokopedia. This research contributes to the growth of intention studies regarding mobile marketplace applications. This research contributes to the development of the Tokopedia Application so that it is more focused on maximizing customer benefits and minimizing user risks.